Sex Differences in the Load-Velocity Profiles of Three Different Row Exercises - Raúl Nieto-Acevedo; Blanca Romero-Moraleda; Almudena Montalvo-Pérez; Carlos García-Sánchez; Moisés Marquina-Nieto; Daniel Mon-López (MDPI AG, 2023)
This study examined the force-velocity profile differences between men and women in three variations of row exercises. Twenty-eight participants (14 men and 14 women) underwent maximum dynamic strength assessments in the free prone bench row (PBR), bent-over barbell row (BBOR), and Smith machine bent-over row (SMBOR) in a randomized order. Subjects performed a progressive loading test from 30 to 100% of 1-RM (repetition maximum), and the mean propulsive velocity was measured in all attempts. Linear regression analyses were conducted to establish the relationships between the different measures of bar velocity and % 1-RM. The ANOVAs applied to the mean velocity achieved in each % 1-RM tested revealed significantly higher velocity values for loads < 65% 1-RM in SMBOR compared to BBOR (p < 0.05) and higher velocities for loads < 90% 1-RM in SMBOR compared to PBR (p < 0.05) for both sexes. Furthermore, men provided significantly higher velocity values than women (PBR 55-100% 1-RM; BBOR and SMBOR < 85% 1-RM; p < 0.05) and significant differences were found between exercises and sex for 30-40% 1-RM. These results confirm that men have higher velocities at different relative loads (i.e., % 1-RM) compared to women during upper-body rowing exercises.